2017
DOI: 10.1159/000484677
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Anti-Leukemia Immunity by Leukemia–Derived Exosomes Via Downregulation of TGF-β1 Expression

Abstract: Background/Aims: Minimal residual leukemia cells (MRLs) are difficult to eradicate through traditional treatment and therefore remain to be a major threat to the long-term survival of leukemia patients. Tumor-derived exosomes (TEXs), which carry tumor associated antigens (TAA), may be a potential cell-free tumor vaccine for the specific eradication of MRLs. However, TEXs are intended to be less immunogenic due to exosomal TGF-β1. To further optimize the efficacy of TEX-based vaccines, we investigated whether e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 41 publications
0
48
0
1
Order By: Relevance
“…Exosomes are endosome-derived vesicles with a diameter of 30~100 nm [9] that are widely involved in tissue repair [10,11] and the inflammatory reaction [12,13]. Carrying signalling molecules [14,15], exosomes have been accepted as markers of disease [16,17] or information vectors [18].…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are endosome-derived vesicles with a diameter of 30~100 nm [9] that are widely involved in tissue repair [10,11] and the inflammatory reaction [12,13]. Carrying signalling molecules [14,15], exosomes have been accepted as markers of disease [16,17] or information vectors [18].…”
Section: Introductionmentioning
confidence: 99%
“…TEXs are not only involved in establishing a favorable microenvironment surrounding the tumor but also induce a comprehensive alteration of the immune system (27,28). A full understanding of TEX immunization includes the observation that TEXs are a source of shared TAA and stimulatory molecules for the innate immune response, which can induce T cell-dependent immunity in mice or human tumor models under some conditions (8)(9)(10)(11)(16)(17)(18). This property makes TEXs novel potential vaccines for the treatment of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, RDE antigen-specific splenic CD8 + T cells displayed stronger cytotoxicity for the autologous tumor cells than the other types of tumor cells at any E/T ratio. In vitro experiments have shown that TEXs may need to rely on host DCs for the induction of an immune response (8)(9)(10)(11)(12)(13)(14); however, TEXs can be taken up by CD8 + T cells, although a lack of DC participation was reported in some experiments, and TEXs can directly induce specific killing activity of CD8 + T cells via exosomal MHC molecules (35). Notably, we observed a dramatic phenomenon in which RDE-stimulated CD8 + T cells displayed a slightly weaker lethality for CT26 cells and 4T1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in order to have efficient vaccination based on TDEs, the TDEs-derived TGF-β1 should be counteracted. 32 It would be a novel exosomes-based tumor vaccination. Moreover, utilizing exosomes can be a helpful strategy to eliminate minimal residual diseases (MRDs).…”
Section: Exosomes Effect On Leukemia Treatmentmentioning
confidence: 99%